Pengaruh Dosis Pupuk Npk (15-15-15) Terhadap Pertumbuhan Bibit Jabon Merah (Anthocephalus macrophyllus Roxb.) Havil) di Pembibitan - Hamzah, Hamzah; Silaen, Rudi Hardi (Jurnal Silva Tropika, 2018)
This research aimes to study the effect of dose NPK fertilizer (15-15-15) provided gradually to growth of Jabon merah seedling (Anthocephalus macrophyllus (Roxb.) Havil) in nursery. The observation was conducted in Research Farm Faculty of Agriculture University of Jambi for 4 months. This study used completely randomized design (CRD) with three replications and five treatments. Dose of fertilizer used was 6 g/seedling, 12 g/seedling, 18 g/seedling, 24 g/seedling and 30 g/seedling. The observed variables are added height, diameter, number of leaves, root dry weight, shoot dry weight, total dry weight and shoot ratio root. Data were analyzed descriptively. The results showed that an increase in the dose of NPK fertilizer (15-15-15) gives a negative impact on the growth of jabon merah seedlings. Dose of 30 g/seedling cause death of jabon merah seedling. Treatments doses of fertilizer 6 g/seedling gives the best results of added height, number of leaves, root dry weight, total dry weight and shoot dry weight. Keywords : Anthocephalus macrophyllus, Dose, NPK fertilizer (15-15-15)